Is multiculturalism bad for women? - Okin, Susan Moller; Cohen, Joshua (Princeton University Press, 1999)
Polygamy, forced marriage, female genital mutilation, punishing women for being raped, differential access for men and women to health care and education, unequal rights of ownership, assembly, and political participation, unequal vulnerability to violence. These practices and conditions are standard in some parts of the world. Do demands for multiculturalism—and certain minority group rights in particular—make them more likely to continue and to spread to liberal democracies? Are there fundamental conflicts between our commitment to gender equity and our increasing desire to respect the customs of minority cultures or religions? In this book, the eminent feminist Susan Moller Okin and fifteen of the world’s leading thinkers about feminism and multiculturalism explore these unsettling questions in a provocative, passionate, and illuminating debate. Okin opens by arguing that some group rights can, in fact, endanger women. She points, for example, to the French government’s giving thousands of male immigrants special permission to bring multiple wives into the country, despite French laws against polygamy and the wives’ own bitter opposition to the practice. Okin argues that if we agree that women should not be disadvantaged because of their sex, we should not accept group rights that permit oppressive practices on the grounds that they are fundamental to minority cultures whose existence may otherwise be threatened. In reply, some respondents reject Okin’s position outright, contending that her views are rooted in a moral universalism that is blind to cultural difference. Others quarrel with Okin’s focus on gender, or argue that we should be careful about which group rights we permit, but not reject the category of group rights altogether. Okin concludes with a rebuttal, clarifying, adjusting, and extending her original position. These incisive and accessible essays—expanded from their original publication in Boston Review and including four new contributions—are indispensable reading for anyone interested in one of the most contentious social and political issues today.
Keywords: 1900-1999; 1990-1999; amérique du nord; amériques; approches et analyses; corps; cours; discipline; droits des femmes*; europe; france; multiculturalisme; phi4336; philosophie; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis

Privilege: Expanding on Marilyn Frye's "Oppression" - Bailey, A. (JOURNAL OF SOCIAL PHILOSOPHY -AUGUSTA-, 1998)
This essay serves as both a response and embellishment of Marilyn Frye's now classic essay " Oppression." It is meant to pick up where this essay left off and to make connections between oppression, as Frye defines it, and the privileges that result from institutional structures. This essay tries to clarify one meaning of privilege that is lost in philosophical discussions of injustice. I develop a distinction between unearned privileges and earned advantages. Clarifying the meaning of privilege as unearned structural advantage makes visible the role white privilege plays in maintaining complex systems of domination such as racism, sexism, heterosexism and classism. Using a critical reading of both Frye and Young's accounts of oppression as a springboard, I develop a definition of privilege as a particular class of unearned advantages. -/- I distinguish my account of privilege from standard legal and philosophical definitions of privilege. The general distinction I make between privileges and advantages rests on three interrelated claims: that benefits granted by privilege are always unearned and conferred systemically to members of dominant social groups; that privileges granted to members of dominant groups solely on the basis of their membership in these groups is never justifiable; and, that privileges have an unconditional value that can be explained not only in terms of immunities, but also in terms of additional benefits
Keywords: 1900-1999; 1990-1999; amérique du nord; amériques; approches et analyses; cours; cycles supérieurs; discipline; discours dominant; fem9000; justice sociale; phi4336; philosophie; premier cycle; privilèges; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis

Feminism and ecological communities: an ethic of flourishing - Cuomo, Chris J. (Routledge, 1998)
Feminism and Ecological Communities presents a bold and passionate rethinking of the ecofeminist movement. It is one of the first books to acknowledge the importance of postmodern feminist arguments against ecofeminism whilst persuasively preseenting a strong new case for econolocal feminism. Chris J.Cuomo first traces the emergence of ecofeminism from the ecological and feminist movements before clearly discussing the weaknesses of some ecofeminist positions. Exploring the dualisms of nature/culture and masculing/feminine that are the bulwark of many contemporary ecofeminist positions and questioning traditional traditional feminist analyses of gender and caring, Feminism and Ecological Communities asks whether women are essentially closer to nature than men and how we ought to link the oppression of women, people of colour, and other subjugated groups to the degradation of nature. Chris J.Cuomo addresses these key issues by drawing on recent work in feminist ethics as well as teh work of diverse figures such as Aristotle, John Dewey, Donna Haraway adn Maria Lugones. A fascinating feature of the book is the use of the metaphor of the cyborg to highlight the fluidity of the nature/culture distinction and how this can enrich econfeminist ethics and politics. An outstanding new argument for an ecological feminism that links both theory and practice, Feminism and Ecological Communities bravely redraws the ecofeminist map. It will be essential reading for all those interested in gender studies, environmental studies and philosophy.
Keywords: approches et analyses; com5170; cours; discipline; environnement; philosophie; postmodernisme; premier cycle; sciences humaines; thématiques; écoféminisme

Body art: performing the subject - Jones, Amelia (University of Minnesota Press, 1998)
An examination of the social and cultural significance of body art by a major new voice. The past few years have seen an explosion of interest in body art, in which the artist's body is integral to the work of art. With the revoking of NEA funding for such artists as Karen Finley, Tim Miller, and others, public awareness and media coverage of body-oriented performances have increased. Yet the roots of body art extend to the 1960s and before. In this definitive book, Amelia Jones explores body art projects from the 1960s and 1970s and relates their impact to the work of body artists active today, providing a new conceptual framework for defining postmodernism in the visual arts. Jones begins with a discussion of the shifting intellectual terrain of the 1950s and 1960s, focusing on the work of Ana Mendieta. Moving to an examination of the reception of Jackson Pollock's "performative" acts of painting, she argues that Pollock is a pivotal figure between modernism and postmodernism. The book continues with explorations of Vito Acconci and Hannah Wilke, whose practices exemplify a new kind of performance that arose in the late 1960s, one that represents a dramatic shift in the conception of the artistic subject. Jones then surveys the work of a younger generation of artists -- including Laurie Anderson, Orlan, Maureen Connor, Lyle Ashton Harris, Laura Aguilar, and Bob Flanagan -- whose recent work integrates technology and issues of identity to continue to expand the critique begun in earlier body art projects. Embracing an exhilarating mix of methodologies and perspectives (including feminism, queer theory, philosophy, psychoanalysis, and literary theory), this rigorous and elegantexamination of body art provides rich historical insight and essential context that rethinks the parameters of postmodern culture.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; approches et analyses; art contemporain; arts; arts visuels et médiatiques; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; performance; philosophie; postmodernisme; premier cycle; périodes historiques; queer; sciences humaines; sexualité; thématiques; théorie de l'art

Excitable speech: A politics of the performance - Butler, Judith (Routledge, 1997)
‘When we claim to have been injured by language, what kind of claim do we make?’ - Judith Butler, Excitable Speech Excitable Speech is widely hailed as a tour de force and one of Judith Butler’s most important books. Examining in turn debates about hate speech, pornography and gayness within the US military, Butler argues that words can wound and linguistic violence is its own kind of violence. Yet she also argues that speech is ‘excitable’ and fluid, because its effects often are beyond the control of the speaker, shaped by fantasy, context and power structures. In a novel and courageous move, she urges caution concerning the use of legislation to restrict and censor speech, especially in cases where injurious language is taken up by aesthetic practices to diminish and oppose the injury, such as in rap and popular music. Although speech can insult and demean, it is also a form of recognition and may be used to talk back; injurious speech can reinforce power structures, but it can also repeat power in ways that separate language from its injurious power. Skillfully showing how language’s oppositional power resides in its insubordinate and dynamic nature and its capacity to appropriate and defuse words that usually wound, Butler also seeks to account for why some clearly hateful speech is taken to be iconic of free speech, while other forms are more easily submitted to censorship. In light of current debates between advocates of freedom of speech and ‘no platform’ and cancel culture, the message of Excitable Speech remains more relevant now than ever.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; cours; discipline; fem1000; performativité; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; états-unis

The flowers in your dustbin: Girls in the North American punk subcultures of the 1990s - Leblanc, Lauraine (Université Emory, 1997)
Girls in male-dominated youth subcultures confront ideologies of gender which remain largely invisible and often tacitly accepted in many women's everyday lives. Punk girls choose to construct their femininity within a highly male-dominated, "masculinist," context; girls are present in such youth subcultures, but the masculine definition of their norms problematizes their participation. Thus, punk girls struggle to accommodate female gender norms within subcultural identities which are deliberately coded as "masculine." Although young women in America encounter the norms of the female gender role on a daily basis, punk girls' negotiations between the norms of femininity and those of punk open these prescriptions to critical examination which they might not otherwise be accorded. In this dissertation, I explore accounts of punk girls' engagements with both mainstream and subcultural gender norms. In constructing this account of girls' lived experiences in the punk subculture, I rely primarily upon the phenomenology, or experiential narrative, of punk girls' everyday lives. I elicited these accounts within the context of conducting participant observation in the punk scenes of four North American cities (Atlanta, Montreal, New Orleans, and San Francisco) from 1993 to 1995, conducting ethnographic interviews with forty punk girls. In the following, I explore various facets of punk girls' engagements with gender norms, including punk girls' narratives of engagement with the subculture; the construction of punk as a discourse of masculinity; punk girls' stylistic, behavioral, and discursive reconstructions of femininity; punk girls' experiences of public harassment and sexual harassment, and their strategic responses to these. I argue that these girls use the punk subculture in order to carry out resistances to varied forms of gender oppression, thereby developing stronger self-concepts in the face of adversity.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; atlanta; discipline; ethnographie; genre; harcèlement sexuel; masculinisme; montréal; mémoires/thèses; nouvelle-orléans; patriarcat; philosophie; périodes historiques; régions géographiques; résistance; san francisco; sciences humaines; systèmes d'oppressions; thématiques; violences

The rejected body: feminist philosophical reflections on disability - Wendell, Susan (Routledge, 1996)
''Susan Wendell has lived with Chronic Fatigue Syndrome (Myalgic Encephalomyelitis) since 1985. In The Rejected Body, she connects her own experience of illness to feminist theory and the literature of disability. The Rejected Body argues that feminist theorizing has been skewed toward non-disabled experience, and that the knowledge of people with disabilities must be integrated into feminist ethics, discussions of bodily life, and the criticism of the cognitive and social authority of medicine.''
Keywords: 1900-1999; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; capacitisme; corps; cours; discipline; inégalités; phi4336; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; états-unis

Feminist contentions: A philosophical exchange - Benhabib, Seyla; Butler, Judith; Cornell, Drucilla; Fraser, Nancy (Thinking gender, 1995)
Ce volume présente un débat entre quatre des plus grandes théoriciennes féministes des États-Unis. Seyla Benhabib, Judith Butler, Drucilla Cornell et Nancy Fraser discutent de certaines des questions clés auxquelles la théorie féministe est confrontée. Chacune articule sa propre position dans un essai initial, puis répond aux autres dans un essai de suivi, rendant possible une conversation entre ces penseuses féministes influentes. Commencé comme un symposium sur la question du féminisme et du postmodernisme, le volume s'est transformé en une discussion sur des questions plus larges telles que l'utilité du postmodernisme en tant que concept théorique; le rôle de la philosophie dans la critique sociale ; comment le récit historique est le mieux conceptualisé ; le statut du sujet du féminisme ; et les effets politiques des différentes formulations de toutes ces questions.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem9000; genre; identités LGBTQIA2+; philosophie; postmodernisme; périodes historiques; régions géographiques; sciences humaines; thématiques; états-unis

Feminism and postmodernism - Ferguson, Margaret; Wicke, Jennifer (Duke University Press, 1994)
This collection of essays explores the significant agreements and tensions between contemporary feminist and postmodern theories and practices. Having brought enormous changes to conceptions of the body, identity, and the media, postmodernity compels the rethinking of many feminist categories, including female experience, the self, and the notion that "the personal is political." Feminist analysis has been equally important, though not always equally acknowledged, as a force within postmodernism. Feminist writings on subjectivity, master narratives, and the socioeconomic underpinnings of the master narrative of theory itself have been particularly influential. This volume traces the crossings and mutual interrogations of these two traditions into the arenas of cultural production, legal discourse, and philosophical thought. Multidisciplinary and international in their collective focus, the essays range from a study of Madonna as an Italian American woman who is revising the cultural meanings of an ethnic feminism to a unique interview with Mairead Keane, the national head of the Women’s Department of the Irish political party Sinn Fein. Turning the prism of postmodern feminism onto such diverse cultural objects as literary and literary critical texts, contemporary film, and music, these essays intervene in debates regarding technology, sexuality, and politics. Challenging modern feminisms to articulate their inescapable relation to postmodern society, this expanded edition of a special issue of boundary 2 also explores ways in which feminism can work as the cutting edge of a global postmodernism. Contributors. Salwa Bakr, Claire Detels, Margaret Ferguson, Carla Freccero, Marjorie Garber, Barbara Harlow, Laura E. Lyons, Anne McClintock, Toril Moi, Linda Nicholson, Mary Poovey, Andrew Ross, David Simpson, Kathyrn Bond Stockton, Jennifer Wicke
Keywords: amériques; approches et analyses; cours; discipline; fem1000; féminisme pop; irlande; philosophie; postmodernisme; premier cycle; régions géographiques; sciences humaines; troisième vague; états-unis; études culturelles

L'identité féminine : biologie ou conditionnement social? - Irigaray, Luce (Femmes : moitié de la terre, moitié du pouvoir, 1994)
Keywords: 1900-1999; 1990-1999; approches et analyses; cours; discipline; europe; fem1000; france; inégalités; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; théories féministes

Feminist epistemologies - Alcoff, Linda Martín.; Potter, Elizabeth (Thinking gender, 1993)
Il s'agit de la première collection de théoriciennes féministes influentes à se concentrer sur le cœur de l'épistémologie traditionnelle, traitant de questions telles que la nature des connaissances et l'objectivité dans une perspective de genre.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem9000; genre; identités LGBTQIA2+; philosophie; point de vue situé; ressource en ligne; sciences humaines; thématiques; épistémologie

What are friends for?: feminist perspectives on personal relationships and moral theory - Friedman, Marilyn (Cornell University Press, 1993)
A contribution to the feminist discussion on moral theory, exploring the debate between moral impartiality and the partiality that characterizes personal relationships, the ethic of care and its relation to justice in a gender asymmetrical society, and the role of intimate friendship in an era of the dissolution of both extended and nuclear families.
Keywords: 1900-1999; 1980-1989; amour; amérique du nord; amériques; approches et analyses; care; cours; discipline; phi2030; philosophie; point de vue situé; premier cycle; périodes historiques; rapports sociaux de sexe; relations amoureuses; régions géographiques; sciences humaines; thématiques; états-unis; éthique

Unmarked: the politics of performance - Phelan, Peggy (Routledge, 1993)
Feminist film theory has made the psychic and political limitations of representational visibility abundantly clear. Yet the Left continues to promote visibility politics as a crucial aspect of progressive struggle. Unmarked examines the fraught relation between political and representational visibility and invisibility within both mainstream and avant-garde art. Suggesting that there may be some political power in an active disappearance from the visual field, Phelan looks carefully at examples of such absences in photography, film, theatre, the iconography of anti-abortion demonstrations, and performance art. A boldly specultative analysis of contemporary culture, Unmarked is a controversial study of the politics of performance. Situating performance theory within emerging theories of psychoanalysis, feminism, and cultural studies, Phelan argues that the non-reproductive power of performance offers a different way of thinking about cultural production and reproduction more generally. Written from and for the Left, Phelan's readings of the work of Robert Mapplethorpe, Cindy Sherman, Mira Schor, Yvonne Rainer, Jennie Livingstone, Tom Stoppard, Angelika Festa and Operation Rescue radically rethink the politics of cultural representation.
Keywords: amériques; approches et analyses; arts; cours; discipline; féminisme pop; har4600; histoire de l'art; histoire et politique; performance; philosophie; premier cycle; psychanalyse; ressource en ligne; régions géographiques; sciences; sciences humaines; sex2283; thématiques; états-unis

Feminists theorize the political - Butler, Judith; Scott, Joan Wallach (Routledge, 1992)
On a dit que l'utilisation de la « théorie » dans l'analyse féministe menaçait le féminisme en tant que force politique. Cette collection de travaux d'éminentes universitaires féministes aborde la question du statut politique de la théorie du poststructuralisme au sein du féminisme. Contre l'idée que l'utilisation du post-structuralisme affaiblit nécessairement le féminisme, « Feminists Theorize the Political » affirme le débat contemporain sur la théorie comme politiquement riche et conséquent. En jetant les bases théoriques du volume, Butler et Scott ont posé un certain nombre de questions à d'éminents juristes, critiques littéraires, philosophes, théoriciens politiques, historiens et théoriciens de la culture. Les essais ne résolvent pas les questions mais génèrent des directions nouvelles et productives pour celles-ci. Le volume dans son ensemble valorise le pouvoir troublant et politique de la théorie. Les essais de "Feminists Theorize the Political" abordent les questions qui émergent de la convergence du féminisme et du poststructuralisme : qu'advient-il de la critique féministe lorsque les fondements traditionnels - l'expérience, l'histoire, les normes universelles - sont remis en question ? La théorie féministe peut-elle problématiser la notion de sujet sans perdre son effectivité politique ? Quelle version du sujet doit être interrogée, et comment ce questionnement ouvre-t-il des possibilités de reformulation de l'agence, du pouvoir et des sites de résistance politique ? Quelles sont les conséquences d'une reformulation spécifiquement féministe de la différence ? Quels sont les usages et les limites d'une critique poststructuraliste de la logique binaire pour la théorisation des différences raciales et de classe, la position du subalterne ? Cette anthologie représente une diversité de travaux théoriques au sein de la théorie féministe à forts enjeux politiques. Bien que tous les auteurs ne souscrivent pas au poststructuralisme (et peu concéderaient que le poststructuralisme est une entreprise monolithique), chacun propose une analyse féministe innovante qui est d'une certaine manière motivée dans et par le défi poststructuraliste. 'Feminists Theorize The Political' aborde une série de préoccupations féministes, y compris la liberté productive, la loi anti-discrimination, le viol et la formulation du pouvoir en termes d'exclusion, de différence et de hiérarchie. chacune propose une analyse féministe innovante qui est en quelque sorte motivée dans et par le défi poststructuraliste. 'Feminists Theorize The Political' aborde une série de préoccupations féministes, y compris la liberté productive, la loi anti-discrimination, le viol et la formulation du pouvoir en termes d'exclusion, de différence et de hiérarchie. chacune propose une analyse féministe innovante qui est en quelque sorte motivée dans et par le défi poststructuraliste. 'Feminists Theorize The Political' aborde une série de préoccupations féministes, y compris la liberté productive, la loi anti-discrimination, le viol et la formulation du pouvoir en termes d'exclusion, de différence et de hiérarchie.
Keywords: 1900-1999; 1990-1999; anthologie; approches et analyses; cours; cycles supérieurs; discipline; fem9000; philosophie; philosophie politique; post-structuralisme; postmodernisme; premier cycle; périodes historiques; sciences humaines; sex3383

J'aime à toi : esquisse d'une félicité dans l'histoire - Irigaray, Luce (Grasset, 1992)
Qui es-tu, toi qui n'es, ne seras jamais moi ni mien ? Je t'écoute comme la révélation d'une vérité irréductible à moi. Tu m'as saluée, reconnue. Tu interroges tes limites. Je te donne du silence où le futur de toi - et peut-être de moi avec toi - peut émerger et se fonder. Je ne m'approche pas immédiatement de toi. Je ne te connaîtrai jamais de manière absolue. Je laisse de l'air, de l'espace, du mystère autour de nous. Éveillée à toi, recueillie, j'invente des paroles qui te touchent de leur souffle sans t'enlever à toi. Cet abord intransitif cherche aide auprès de l'univers, de la beauté, de la sagesse, de l'Histoire. En cette uvre déjà, j'aime à toi. Puisse ce " à " garder l'intention entre nous encore et toujours vive, berceau de l'être que notre transcendance l'un à l'autre enfante. " Après une critique de la maîtrise de notre culture par le genre masculin et la définition de médiations nécessaires à la constitution du sujet féminin, Luce Irigaray élabore ici une dialectique de l'intersubjectivité fondée sur la différence sexuelle. J'aime à toi marque donc un nouveau temps dans l'ouvre de la philosophe, le premier ayant été ouvert par Speculum, De l'autre femme.
Keywords: 1900-1999; 1980-1989; cours; différence des sexes; discipline; europe; fem1000; france; philosophie; premier cycle; psychologie; périodes historiques; régions géographiques; sciences humaines; sujet féminin; thématiques; écriture des femmes*

La nature humaine est deux - Irigaray, Luce (J'aime à toi : esquisse d'une félicité dans l'histoire, 1992)
Keywords: 1900-1999; 1980-1989; cours; différence des sexes; discipline; europe; fem1000; france; philosophie; premier cycle; psychologie; périodes historiques; régions géographiques; sciences humaines; sujet féminin; thématiques; écriture des femmes*

Rethinking masculinity: philosophical explorations in light of feminism - May, Larry; Strikwerda, Robert A.; Hopkins, Patrick D. (New feminist perspective series, 1992)
Are men naturally aggressive? What makes a good father? How can men form intimate friendships? In the new edition of this popular anthology, seventeen philosophers explore these and other questions that relate to what it means to be a man, including questions about pornography and homosexuality. New essays look at masculinity and violence, research on differences between men's and women's brains, impotence, sexual ambiguity, and whether black men have a moral duty to marry black women.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; histoire et politique; masculinité; masculinités; patriarcat; philosophie; premier cycle; rapports sociaux de sexe; sciences humaines; soc2014; systèmes d'oppressions; thématiques

"Chapitre I".De l'assujettissement des femmes. - Mill, John Stuart (De l'assujettissement des femmes, 1992)
Keywords: 1800-1899; approches et analyses; cours; discipline; discours dominant; droits des femmes*; europe; fem1000; philosophie; premier cycle; périodes historiques; ressource en ligne; royaume-uni; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques

De l'assujettissement des femmes. - Mill, John Stuart (Arenes, 1992)
L´écrivain britannique John Stuart Mill était l´un des premiers écrivains masculins à se positionner pour l´égalité des sexes et à défendre la libération des femmes. Il se pencha sur la liberté économique des femmes et était de l´avis que le rôle d´une femme dans le mariage devait évoluer. Le livre « De l’assujettissement des femmes » est un classique de la littérature féministe. Le philosophe et politicien britannique John Stuart Mill (1806+1873) est un des penseurs libéraux les plus importants du 19e siècle. Il est particulièrement connu pour ses théories d´utilitarisme. Il s´est occupé de divers sujets politiques et philosophiques, dont les concepts de liberté et d´égalité des sexes.
Keywords: 1800-1899; approches et analyses; cours; discipline; discours dominant; droits des femmes*; europe; fem1000; phi4336; philosophie; premier cycle; périodes historiques; ressource en ligne; royaume-uni; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques

Le sujet et l’auteur ou lire « l’autre femme » - Collin, Françoise (Les cahiers du CEDREF, 1990)
La réflexion que j'ébaucherai ici est issue de mon trouble devant une question qui m'a été récemment posée, qui est souvent posée aux femmes qui écrivent, et qu'elles se posent : « est-ce que tu écris en tant que femme ? ». De toute évidence la question ne porte pas sur le fait de savoir si c’est une femme qui écrit - puisqu’elle le présuppose - mais si cette femme écrit « en tant que femme ». Elle implique donc qu'une femme pourrait ne pas écrire « en tant que femme », que le sujet et l'auteur ne coïncident pas nécessairement, qu'elles entretiennent des rapports pour le moins incertains et variables.
Keywords: cours; cycles supérieurs; discipline; fem9000; philosophie; ressource en ligne; sciences humaines; thématiques; écriture des femmes*

Social Criticism without Philosophy: An Encounter between Feminism and Postmodernism - Fraser, Nancy; Nicholson, Linda J. (Feminism/postmodernism, 1990)
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; discipline; fem1000; philosophie; postmodernisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; théories culturelles; états-unis

Gender and knowledge: Elements of a postmodern feminism - Hekman, Susan J. (Northeastern University Press, 1990)
The aim of the book is to explore the connection between two perspectives that have had a profound effect upon contemporary thought: post-modernism and feminism. Through bringing together and systematically analysing the relations between these, Hekman is able to make a major intervention into current debates in social theory and philosophy. The critique of Enlightenment knowledge, she argues, is at the core of both post-modernism and feminism. Each also offers a basis for critical reflections about the other. In particular, post-modern philosophy provides a means of criticizing aspects of contemporary feminism and thus contributing to the development of a more sophisticated approach to current feminist issues.
Keywords: 1700-1799; 1900-1999; 1980-1989; approches et analyses; cours; discipline; europe; fem1000; france; philosophie; postmodernisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; études culturelles

Feminism/postmodernism - Nicholson, Linda J. (Thinking gender, 1990)
In this anthology, prominent contemporary theorists assess the benefits and dangers of postmodernism for feminist theory. The contributors examine the meaning of postmodernism both as a methodological position and a diagnosis of the times. They consider such issues as the nature of personal and social identity today, the political implications of recent aesthetic trends, and the consequences of changing work and family relations on women's lives. Contributors: Seyla Benhabib, Susan Bordo, Judith Butler, Christine Di Stefano, Jane Flax, Nancy Fraser, Donna Haraway, Sandra Harding, Nancy Hartsock, Andreas Huyssen, Linda J. Nicholson, Elspeth Probyn, Anna Yeatman, Iris Young.
Keywords: 1900-1999; 1980-1989; amériques; anthologie; approches et analyses; cours; discipline; fem1000; philosophie; postmodernisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; théories culturelles; théories féministes; états-unis

Justice, gender, and the family - Okin, Susan Moller (Basic Books, 1989)
This work is a feminist critique of modern political theory. The author sets out to show how the failure to apply theories of justice to the family not only undermines democratic values but has led to a major crisis over gender-related issues.
Keywords: amériques; approches et analyses; care; discipline; division sexuelle du travail; droit; droits des femmes*; famille; genre; mariage; maternité; militance; patriarcat; philosophie; ressource en ligne; régions géographiques; science politique et droit; sciences humaines; stéréotypes de genre; systèmes d'oppressions; thématiques; travail; états-unis

Toward a Feminist Theory of Disability - Wendell, Susan (Hypatia, 1989)
We need a feminist theory of disability, both because 16 percent of women are disabled, and because the oppression of disabled people is closely linked to the cultural oppression of the body. Disability is not a biological given; like gender, it is socially constructed from biologically reality. Our culture idealizes the body and demands that we control it. Thus, although most people will be disabled at some time in their lives, the disabled are made "the other," who symbolize failure of control and the threat of pain, limitation, dependency, and death. If disabled people and their knowledge were fully integrated into society, everyone's relation to her/his real body would be liberated.
Keywords: 1900-1999; 1980-1989; EDI; approches et analyses; bioéthique; care; corps; cours; discipline; intersectionnalité; philosophie; premier cycle; périodes historiques; ressource en ligne; santé; sciences humaines; sex1911; sex1920; thématiques; éthique; études critiques du handicap

Cultural feminism versus post-structuralism: The identity crisis in feminist theory - Alcoff, Linda (Signs, 1988)
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem9000; femmes*; identité sexuelle; philosophie; post-structuralisme; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; états-unis; études culturelles

Traité de la morale et de la politique 1693: la Liberté - Suchon, Gabrielle (La Philosophe, 1988)
« Vous prendrez garde, mon lecteur, qu'encore que la Morale et la Politique ne soient pas traitées en ce livre selon la méthode ordinaire des Philosophes et des Théoriciens, l'on peut néanmoins y reconnaître les principales matières de ces deux grands sujets. » Voici présenté par Gabrielle Suchon elle-même, son Traité de Morale et de Politique, publié à Lyon en 1693. Le présent ouvrage est la réédition de la première partie, la Liberté, cette « qualité savoureuse ». Avec Gabrielle Suchon, le sexe - ou, comme elle l'écrit : le Sexe - fait son entrée en philosophie. Sous sa plume, la liberté perd la figure abstraite d'un concept métaphysique pour se transformer en une question brûlante, née d'une douloureuse privation : quelle liberté pour le Sexe ? Comme le souligne Séverine Auffret, Gabrielle Suchon ne se situe pourtant pas dans une lignée féministe. Nourrie de Platon, d'Aristote et des Écritures, c'est bien dans le champ philosophique qu'elle se meut et qu'elle vient « fêter » quelque chose. Agrégée de philosophie, Séverine Auffret a entrepris de faire éditer l'oeuvre de Gabrielle Suchon (1632-1703).
Keywords: 1600-1699; approches et analyses; cours; discipline; discours dominant; europe; fem1000; france; philosophie; premier cycle; périodes historiques; régions géographiques; savoirs; sciences humaines; systèmes d'oppressions

Il n'y a pas de cogito-femme - Collin, Françoise (L'émergence d'une culture au féminin, 1987)
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem9000; histoire et politique; interdisciplinarité; philosophie; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; thématiques; études culturelles; études littéraires

Invisible Work - Daniels, Arlene Kaplan (Social Problems, 1987)
Our folk understanding of “work” focuses on those activities you “have to do” to get paid for them. Women's work is correspondingly devalued, for it is either unpaid or limited by the demands of the unpaid work in the home. This understanding also includes a moral force. One should contribute to society by working. This paper shows the restrictiveness of these commonsense understandings and discusses the kinds of work that consequently disappear from view. I focus especially on the work involved in the social construction of daily life and in the maintenance and development of institutions. Finally, I present the rationale for expanding the concept of work to include many activities not previously considered in the folk concept: a keener awareness of the work involved in social constructions serves to dignify the labor and engender respect for the workers who do it.
Keywords: discipline; histoire et politique; philosophie; projet charge mentale; sciences humaines; thématiques; travail; travail invisible

La dialectique de la reproduction - O'Brien, Mary (Les éditions du remue-ménage, 1987)
Dans La dialectique de la reproduction, essai de philosophie féministe, Mary O’Brien montre comment la pensée masculine et les institutions patriarcales ont été édifiées pour contrecarrer l’incertitude de la paternité et pour médiatiser l’exclusion des hommes du travail reproductif.
Keywords: 1900-1999; EDI; approches et analyses; care; corps; cours; discipline; division sexuelle du travail; fem1000; justice reproductive; philosophie; premier cycle; périodes historiques; sciences humaines; thématiques; travail du care

Éthique de la différence sexuelle - Irigaray, Luce (La Critique, 1984)
« L’homme et la femme demeurent plus étrangers l’un à l’autre que ne le ont à chacun l’animal, la plante, la pierre, l’univers, les dieux. Cet irréductible de l’un à l’autre s’oublie sans cesse et s’organise en mondes bâtis dans la méconnaissance. Le langage, les échanges en général fonctionnent comme si ces deux moitiés du monde se connaissaient, se parlaient, se partageaient. À peine se font-elles signe de chaque côté d’un miroir qui n’appartient ni à l’une ni à l’autre, d’un abîme infernal ou céleste, d’une proximité que plus rien ne signifie. À moins qu’elles ne se détournent délibérément l’une de l’autre, ou ne tentent de se détruire dans le vertige de quelque renversement dialectique. Ni la femme ni l’homme n’ont construit un territoire qui leur permette d’habiter et cohabiter leur corps, leur chair, de s’étreindre, s’aimer, créer ensemble. Mais la constitution d’une éthique sexuée est toujours reportée à plus tard. Elle emprunte d’étranges détours. S’arrête à l’écologie animale, considère le sexe des végétaux, analyse le comportement de nos cellules, s’efforce de connaître toutes espèces ou genres de mêmes et d’autres selon la taille, la forme, la couleur, la quantité, le nombre... Tout, sauf ce si proche de nous que nous ne le percevons pas et que, le touchant, nous n’abordons souvent qu’à notre nuit. Tant nous fait défaut ce qui dit nos puissances sensibles, leur architecture, leurs abords, leurs seuils, leurs passages du plus intime au plus lointain, en nous, entre nous. La différence sexuelle comme enjeu théorique et pratique est encore abandonnée aux sciences et techniques “ secondes ” : médecines, arts, modes. Restaurations, reproductions, voiles, masques d’un original qui reste dans l’ombre, et qui vaut d’être interrogé avant d’être imputé à Dieu, ou quelque Autre qui nous fait loi. Qui suis-je ? Qui es-tu ? En quoi consiste l’insurmontable de notre différence ? Quelles sont nos conditions de possibilité de vie, de beauté, de raison commune ? Ces questions s’imposent à notre époque. Mais elles suscitent les polémiques et les refus de qui se veut, se croit, ou s’ignore monopole d’une “ philosophie première ” – Vérité. » Luce Irigaray
Keywords: 1900-1999; 1980-1989; cours; différence des sexes; discipline; europe; fem1000; france; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; éthique

Pour un féminisme critique - Braidotti, Rosi (Les Cahiers du GRIF, 1983)
Keywords: 1900-1999; 1980-1989; cours; cycles supérieurs; discipline; fem9000; philosophie; périodes historiques; ressource en ligne; sciences humaines

La même et les différences - Collin, Françoise (Les Cahiers du GRIF, 1983)
Keywords: cours; cycles supérieurs; discipline; fem9000; philosophie; ressource en ligne; sciences humaines; thématiques; écriture des femmes*

« Oppression, » dans The politics of reality, - Frye, Marilyn (The politics of reality: essays in feminist theory, 1983)
Politics of Reality includes nine essays that examine sexism, the exploitation of women, the gay rights movement and other topics from a feminist perspective. The essays "The Problem That Has No Name" and "A Note On Anger" have been translated into Spanish by Maria Lugones for circulation in la Asociacion Argentina de Mujeres en Filosofia.
Keywords: 1900-1999; 1970-1979; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem9000; hétérosexisme; identités LGBTQIA2+; intersectionnalité; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; états-unis

Discovering reality : feminist perspectives on epistemology, metaphysics, methodology, and philosophy of science - Harding, Sandra G.; Hintikka, Merril B. (D. Reidel, 1983)
This collection of essays, first published two decades ago, presents central feminist critiques and analyses of natural and social sciences and their philosophies. This work provides a splendid opportunity for upper-level undergraduate and graduate students in philosophy and the social sciences to explore some of the most intriguing and controversial challenges to disciplinary projects and to public policy today.
Keywords: approches et analyses; cours; discipline; discours dominant; fem1000; philosophie; point de vue situé; premier cycle; sciences humaines; systèmes d'oppressions; épistémologie

The feminist standpoint: Developing the ground for a specifically feminist historical materialism - Hartstock, Nancy (Discovering reality: Feminist perspectives on epistemology, metaphysics, methodology, and philosophy of science, 1983)
Keywords: approches et analyses; cours; discipline; fem1000; féminisme matérialiste; philosophie; point de vue situé; premier cycle; sciences humaines; épistémologie

The death of nature: Women, ecology and the scientific revolution - Merchant, Carolyn (New York : Harper & Row, 1983)
Un examen de la révolution scientifique qui montre comment la vision mécaniste du monde de la science moderne a sanctionné l'exploitation de la nature, l'expansion commerciale sans retenue et un nouvel ordre socio-économique qui subordonne les femmes.
Keywords: approches et analyses; capitalisme; discipline; environnement; histoire; histoire des sciences; histoire et politique; incontournable; patriarcat; philosophie; progrès; projet charge mentale; santé; sciences humaines; systèmes d'oppressions; thématiques; violences; violences envers la nature; violences envers les femmes*; écoféminisme

Histoire de la sexualité I. La volonté de savoir - Foucault, Michel (Bibliothèque des histoires, 1976)
"L'Histoire de la sexualité, articulée en trois volumes (La volonté de savoir, L'usage des plaisirs et Le souci de soi), prolonge les recherches entreprises avec L'archéologie du savoir et Surveiller et punir. Michel Foucault concentre ses analyses sur la constellation de phénomènes que nous désignons par le « sexe » et la sexualité. L'axe de cette entreprise n'est pas de s'ériger contre une « répression » de la sexualité afin de la « libérer », mais de montrer comment la vie sexuelle a enclenché une volonté systématique de tout savoir sur le sexe qui s'est systématisée en une « science de la sexualité », laquelle, à son tour, ouvre la voie à une administration de la vie sexuelle sociale, de plus en plus présente dans notre existence.Foucault fait ainsi l'archéologie des discours sur la sexualité (littérature érotique, pratique de la confession, médecine, anthropologie, psychanalyse, théorie politique, droit, etc.) depuis le XVIIIe siècle et, surtout, au XIXe, dont nous héritons jusque dans les postures récentes de « libération sexuelle ». L'attitude de censure et celle d'affranchissement se rencontrent finalement dans le même type de présupposé : le sexe serait cause de tous les phénomènes de notre vie comme il commanderait l'ensemble de l'existence sociale."-- Site de l'éditeur.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; analyse de discours; approches et analyses; cours; discipline; discours dominant; foucault; his4860; histoire; histoire de la sexualité; occident; philosophie; post-structuralisme; postmodernisme; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; sciences humaines; sex1183; sexe; sexualité; systèmes d'oppressions; thématiques

L’hypothèse répressive - Foucault, Michel (Histoire de la sexualité. 1. La volonté de savoir, 1976)
"L'Histoire de la sexualité, articulée en trois volumes (La volonté de savoir, L'usage des plaisirs et Le souci de soi), prolonge les recherches entreprises avec L'archéologie du savoir et Surveiller et punir. Michel Foucault concentre ses analyses sur la constellation de phénomènes que nous désignons par le « sexe » et la sexualité. L'axe de cette entreprise n'est pas de s'ériger contre une « répression » de la sexualité afin de la « libérer », mais de montrer comment la vie sexuelle a enclenché une volonté systématique de tout savoir sur le sexe qui s'est systématisée en une « science de la sexualité », laquelle, à son tour, ouvre la voie à une administration de la vie sexuelle sociale, de plus en plus présente dans notre existence.Foucault fait ainsi l'archéologie des discours sur la sexualité (littérature érotique, pratique de la confession, médecine, anthropologie, psychanalyse, théorie politique, droit, etc.) depuis le XVIIIe siècle et, surtout, au XIXe, dont nous héritons jusque dans les postures récentes de « libération sexuelle ». L'attitude de censure et celle d'affranchissement se rencontrent finalement dans le même type de présupposé : le sexe serait cause de tous les phénomènes de notre vie comme il commanderait l'ensemble de l'existence sociale."-- Site de l'éditeur.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; analyse de discours; approches et analyses; cours; discipline; discours dominant; foucault; histoire; occident; philosophie; post-structuralisme; postmodernisme; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; sciences humaines; sex1183; sexe; sexualité; systèmes d'oppressions; thématiques

La femme indépendante - Beauvoir, Simone de (Le Deuxième sexe: l'expérience vécue, 1949)
Keywords: 1900-1999; 1940-1949; cours; discipline; europe; fem1000; france; lit3220; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines

Le deuxième sexe. Conclusion - Beauvoir, Simone de (Le Deuxième sexe: l'expérience vécue, 1949)
Keywords: 1900-1999; 1940-1949; cours; discipline; europe; fem1000; france; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; thématiques; écriture des femmes*

Le deuxième sexe. Introduction - Beauvoir, Simone de (Le Deuxième sexe: les faits et les mythes, 1949)
Keywords: 1900-1999; 1940-1949; cours; discipline; europe; fem1000; france; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; thématiques; écriture des femmes*

Le deuxième sexe : l'expérience vécue - Beauvoir, Simone de (Gallimard, 1949)
Dans ce second volume, Simone de Beauvoir entreprend " d'étudier avec soin le destin traditionnel de la femme ", c'est à dire de " situer " la femme. " Comment la femme fait-elle l'apprentissage de sa condition, comment l'éprouve-t-elle, dans quel univers se trouve-t-elle enfermée, quelles évasions lui sont permises, voilà ce que je chercherai à décrire. " D'abord sa formation : dans l'enfance, dans l'adolescence, dans l'initiation sexuelle, tout semble disposé, agencé, pour creuser davantage le fossé naturel qui la sépare de l'homme, pour transformer des différences en inégalité, et cette inégalité en infériorité. Ensuite sa situation : Simone de Beauvoir décrit la femme dans le mariage, avec ses prémisses, ses traditions, ses conséquences ; dans la maternité ; dans la prostitution, dans la société ; dans le vieillissement et la vieillesse. Enfin elle envisage les problèmes qui se posent aux femmes qui " héritant d'un lourd passé, s'efforcent de forger un avenir nouveau "
Keywords: 1900-1999; 1940-1949; cours; cycles supérieurs; discipline; europe; fem1000; fem7000; france; histoire et politique; incontournable; lit3220; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; sex3383; thématiques; écriture des femmes*

Le deuxième sexe : les faits et les mythes - Beauvoir, Simone de (Idées, 1949)
«Nous commencerons par discuter les points de vue pris sur la femme par la biologie, la psychanalyse, le matérialisme historique. Nous essaierons de montrer ensuite positivement comment la «réalité féminine» s'est constituée, pourquoi la femme a été définie comme l'Autre et quelles en ont été les conséquences du point de vue des hommes. Alors nous décrirons du point de vue des femmes le monde tel qu'il leur est proposé ; et nous pourrons comprendre à quelles difficultés elles se heurtent au moment où, essayant de s'évader de la sphère qui leur a été jusqu'à présent assignée, elles prétendent participer au mitsein humain». Simone de Beauvoir.
Keywords: 1900-1999; 1940-1949; cours; discipline; europe; fem1000; france; har4600; histoire et politique; incontournable; lit3220; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; sex3383; thématiques; écriture des femmes*